2019
DOI: 10.1161/circresaha.118.313533
|View full text |Cite
|
Sign up to set email alerts
|

PATJ Low Frequency Variants Are Associated With Worse Ischemic Stroke Functional Outcome

Abstract: Rationale: Ischemic stroke (IS) is among the leading causes of adult disability. Part of the variability in functional outcome after stroke has been attributed to genetic factors but no locus has been consistently associated with stroke outcome. Objective: Our aim was to identify genetic loci influencing the recovery process using accurate phenotyping to produce the largest genome-wide association study (GWAS) in IS recovery to date. Methods and Results: A 12-cohort, two-phase (discovery-replication and joint)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 21 publications
0
70
1
Order By: Relevance
“…Previous studies showed that epithelial-mesenchymal transition (EMT) markers SANIL and ZEB1 could transcriptionally inhibit PATJ expression in MDCK and MDA-MB-231 cells (Aigner et al, 2007;Whiteman et al, 2008). PATJ SNP variants were associated with worse outcomes in ischemic stroke patients (Mola-Caminal et al, 2019). However, the cause of PATJ downregulation in ccRCC requires future investigation.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies showed that epithelial-mesenchymal transition (EMT) markers SANIL and ZEB1 could transcriptionally inhibit PATJ expression in MDCK and MDA-MB-231 cells (Aigner et al, 2007;Whiteman et al, 2008). PATJ SNP variants were associated with worse outcomes in ischemic stroke patients (Mola-Caminal et al, 2019). However, the cause of PATJ downregulation in ccRCC requires future investigation.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, about long-term stroke outcome, two GWAS studies have been published with remarkable results. The GODS (Genetic contribution to functional Outcome and Disability after Stroke) study detected that PATJ (Pals1-associated tight junction) low-frequency variants were associated with worse IS functional outcome [ 43 ]. In the GISCOME study, with more than 6000 participants, it was showen that intronic variant rs1842681 in LOC105372028 had a significant association with functional outcomes 60–90 days after stroke [ 44 ].…”
Section: Genetics and Inflammation In Post Stroke Recoverymentioning
confidence: 99%
“…Additionally, in reference to long-term stroke outcome, two GWAS (Genetic contribution to functional Outcome and Disability after Stroke [GODS] [7] and Genetics of Ischemic Stroke functional outCOME [GISCOME] [8] studies, with 1,791 and 6,165 participants, respectively) have been recently published with remarkable results. One study [7] had found a locus located within a candidate gene, confirmed by an external replication. These studies are beginning to clarify the influence of genetics on patient recovery, which can help us to understand all the mechanisms involved.…”
Section: Variables Associated With Acute Outcomementioning
confidence: 99%
“…Several genome-wide association studies (GWAS) have found genes associated with stroke risk and have been confirmed in independent studies [4-6]. However, with the exception of two recent GWAS [7,8], the studies performed to find genetic variables associated with stroke outcome are candidate gene studies that have not been consistently replicated [9].…”
Section: Introductionmentioning
confidence: 99%